Horizontal Ridge Augmentation and Contextual Implant Placement with a Resorbable Membrane and Particulated Anorganic Bovine Bone-Derived Mineral - Ferdinando Attanasio; Andrea Pacifici; Amerigo Giudice; Antonella Polimeni; Luciano Pacifici (Case Reports in Dentistry)
Alveolar ridge deficiency is considered a major limitation for successful implant placement. Various approaches have been developed to horizontal augmentation of bone volume. This case report presents the medium-term results of one-stage guided bone augmentation using an anorganic bovine bone (70%) and autologous bone (30%), placed in layers, in association with resorbable collagen membrane for a subsequent implant placement. The patient presented with a localized horizontal ridge defect in the posterior zone of the jaw. The clinical and radiographic presentations, as well as relevant literature, are presented.